Analysing Nonaka's “Knowledge management” theory in the joint venture enterprise in Vietnam: The Case of Dragon Logistics Co., Ltd. - Dao, Thi Thanh Huyen (ĐHQG, 2016)
Nowadays, "Knowledge Management" has become increasingly important in the modern business environment. This study aims to give the detailed understanding of this issue, to describe and explain the knowledge creating process in joint venture companies in Vietnam